Dendritic Cell-Based Vaccine Efficacy: Aiming for Hot Spots - Pizzurro, Gabriela Andrea; Barrio, María Marcela (Frontiers in Immunology, 2015)
Many approaches for cancer immunotherapy have targeted dendritic cells (DC), directly or indirectly, for the induction of antitumor immune responses. DC-based vaccines have been developed using a wide variety of ex vivo DC culture conditions, antigen source and loading strategies, maturation agents and routes of vaccination. Adjuvants are used to activate innate immune cells at the vaccine injection site, to promote antigen transport to the draining lymph nodes (LNs) and to model adaptive immune responses. Despite years of effort, the effective induction of strong and durable antitumor T cell responses in vaccinated patients remains a challenge. The study of vaccine interactions with other immune cells in the LNs and, more recently, in the injection site has opened new doors for understanding antitumor effector T cell licensing and function. In this review, we will briefly discuss the relevant sites and up-to-date facts regarding possible targets for antitumor vaccine refinement. We will focus on the processes taking place at the injection site, adjuvant combinations and their role in DC-based vaccines LN homing and modeling vaccine-induced immune responses capable of controlling tumor growth and generating immune memory.